The black box of biology : a history of the molecular revolution - Morange, Michel (Harvard University Press, 2020)
"Over the past forty years a molecular vision has transformed biology. What began as an attempt to understand and explain life by looking at organisms at the microscopic level soon led to the rapid development of pathbreaking new technologies and discoveries that would change our understanding of science. In The Black Box of Biology Michel Morange shows that what led to this incredible transformation of biology was not an accumulation of new results, but the molecularization of a large part of biology. The expansion led to a cluster of explanatory tools and mechanisms used across biology and medicine. Yet, it was the fusion of the principles and concepts of molecular biology with those of other subdisciplines that led to the most decisive changes, including the discoveries of regulatory RNAs, the development of massive scientific programs like the Human Genome sequencing program, and the emergence of new disciplines like synthetic biology, systems biology, and epigenetics. Yet the progress was not one sided. Morange reveals that molecular biology opened the black box of biology, and in turn, the discipline has been enriched by its expansion"--